Did rent deregulation alter tenure choice decisions in the Czech Republic?1. Issue 2 (9th February 2016) - Tsharakyan, Ashot; Zemčík, Petr
Abstract: Our study is the first that explicitly links rent deregulation and the choice between owning and renting (the tenure choice) using household decisions over a 1‐year period. The rent deregulation process in the Czech Republic started in 2006, two years after joining the European Union. By design, the maximum regulated rent appreciation depended explicitly on real estate prices, which accelerated the pace of deregulation due to rapidly rising prices at the time. A unique dataset enables us to track the tenure choice of households from consumption surveys for subsequent years. The proportion of households that switched from renting to owning sharply increased among renters of regulated apartments. We show that this change was caused by the deregulation process. In contrast, rent deregulation makes owners and renters paying market rent less likely to change ownership status.